Chapter The International Adult Education Academy and Its Contribution to Professionalisation in Adult Education - Breitschwerdt, Lisa (Studies on Adult Learning and Education, 2023)
Planning and designing lifelong teaching-learning processes requires well-educated professionals in adult and continuing education. Against the background of changing social structures, they must be able to act confidently in interdisciplinary, cooperative and unpredictable interaction situations. This requires the development of professionalism in adult education with respect to the following perspectives: 1) interdependencies within the multi-level system of adult education, 2) inference between academic knowledge and adult educational practice, and 3) mediation processes between different social logics of action. Using the example of the International Adult Education Academy, we present and discuss ways of referencing the three perspectives of professionalism in the academic professionalisation of adult education.